2019
DOI: 10.1590/1980-265x-tce-2018-0197
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Role Strain in Informal Caregivers for the Elderly

Abstract: Objective: to analyze the frequency of the “caregiver role strain” nursing diagnosis in informal caregivers for the elderly, the defining characteristics and the related factors. Method: a cross-sectional, descriptive study carried out with 99 informal caregivers for elderly residents living in the areas covered by five units of the Family Health Strategy of Cuiabá, Mato Grasso, Brazil. Data collect took place between July and September 2017, through home interviews. A questionnaire elaborated from the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(55 reference statements)
0
4
0
2
Order By: Relevance
“…The first contained sociodemographic and care context data. The second presented the list of defining characteristics, with each participant being asked to inform to what extent each characteristic was indicative of their feelings and/or behaviors, with five answer options: nothing characteristic of me (1); very uncharacteristic of me (2); characteristic in some way (3); quite characteristic (4); and very characteristic (5). Presence of the defining characteristic was considered when a score ≥ 3 was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first contained sociodemographic and care context data. The second presented the list of defining characteristics, with each participant being asked to inform to what extent each characteristic was indicative of their feelings and/or behaviors, with five answer options: nothing characteristic of me (1); very uncharacteristic of me (2); characteristic in some way (3); quite characteristic (4); and very characteristic (5). Presence of the defining characteristic was considered when a score ≥ 3 was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Aspects related to the caregiver's conditions and to the negative impacts of this practice on their own lives have been the object of several studies nowadays. In these research studies, care recipients are very diverse: older adults 2 , people with dementia [3][4][5] , physical dependence 6 or cancer [7][8] and people in a palliative care situation [9][10] among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is emphasized that the actions need to be concentrated, mainly, in the home environment, contemplating guidance on care, information on the family's health condition, in addition to adaptations in the physical environment, which can facilitate daily life and also accept caregivers' demands, promote a qualified listening of feelings and difficulties they face 3 .…”
Section: /16mentioning
confidence: 99%
“…Frequently, the demands of these individuals go unnoticed by health professionals. A study carried out with informal caregivers of older adults identified that most participants had difficulty in exercising their role, which can negatively impact the health of all involved and the quality of care provided 3 .…”
Section: Introductionmentioning
confidence: 99%
“…O distanciamento do convívio com a comunidade é tolerado de forma diferente pelos grupos de idosos que possuem companhia, seja ela de familiares, cônjuges ou amigos, lidando com as consequências desse isolamento de forma mais branda. No entanto, idosos que vivem sozinhos ou em ILPs, que têm seu contato reduzido com familiares ou mesmo com a sociedade, sofrem as consequências do distanciamento social de forma mais intensa [23][24].…”
Section: Isolamento Social Dos Idosos Em Tempos De Pandemiaunclassified